PENGEMBANGAN PROTOTYPE SISTEM UJIAN BERBASIS COMPUTER BASED TEST (CBT) PADA PROGRAM STUDI TEKNIK INFORMATIKA POLITEKNIK NEGERI AMBON - CARYL ALYONA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
One of the uses of information technology in education is by building a Computer Based Test (CBT) application. The implementation of CBT is very much needed in exam activities in the lecture environment, because with the implementation of this exam, it makes it very easy in the correction phase and can minimize cheating, including question leakage, cheating on exams and even changes in exam scores. Development of a prototype examination system in the Computer-based Ambon State Polytechnic Informatics Engineering study program or also known as the Computer Based Test (CBT) means the test implementation system uses a computer as the test medium. The implementation of the CBT exam is considered very helpful for education providers. The method used in building this application is a prototype. By using this application it makes it easier for lecturers to perform the retest process efficiently